The impact of Covid-19 and Russia-Ukraine war on food prices in fragile countries: Misfortunes never come singly - Samba Diop; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The objective of the paper is to evaluate whether there is a change in the level or trend of food prices in fragile countries following the Covid-19 pandemic and the Russia-Ukraine war. The empirical evidence is based on Interrupted Time Series Analysis. The following findings are established. Firstly, an immediate and sustained positive effect is noted, indicating that for each month that passes after the Covid-19 and Russia-Ukraine war, food prices increase in most of the fragile countries. Secondly, if the Covid-19 and the Russia-Ukraine war had not happened, the price level and its trend would have been at a significantly lower level in fragile countries. Thirdly, the Russia-Ukraine war intervention period slope is significantly and considerably higher than that of the Covid-19 indicating that the Russia-Ukraine war has increased food prices in fragile countries more proportionately than the Covid-19 pandemic did.
Keywords: F52; K42; O17; O55; P16; 330; Covid-19; Russia-Ukraine war; food prices; fragile countries